Development of snake ladder instructional media using STAD cooperative model for class VIII MTS students - Een Ibrahim (Universitas Negeri Yogyakarta, 2021)
This study aimed to determine the effectiveness of snake ladders learning media that was developed using the Student Teams Achievement Divisions (STAD) cooperative learning model in Physics learning with Sound material in class VIII MTs. This research was conducted at MTs Cendekia Muhammadiyah Kotamobagu in the 2018/2019 academic year. The research method used was the research and development (RnD) method consisted of seven stages, i.e.: planning, initial design media, development of media, validation of media, revision, test, and analysis and final revision. In the validation stage, the learning media is validated by media and material experts. The learning media was tried out to students in class VIII MTs as many as 28 students. The result showed that the learning media was viable with averages of 4.03 and 4.54 with percentages of 80.6 (good) and 90.8 (very good) from the material and media experts, respectively. The effectiveness of the learning model can be seen in students’ attractiveness to the snake ladder media with the percentage value above 61% (strongly agree). This means that the snake ladder media obtained an outstanding response on students’ completing the learning, which reached 89.29%. Hence, the snake ladder learning media was eligible for use in the learning process.